TECHNIQUE OF SURGERY ON THE THORACIC LYMPHATIC DUCT AND THE CELLULAR COMPOSITION OF THE CENTRAL LYMPH OF GOATS - Narziev Nurmuhammad Bakhtiyorovich (Journal Park Publishing, 2025)
The article presents the results of a study concerning the topographic anatomy of the thoracic lymphatic duct in goats. The thoracic duct (ductus throracicus) is the main lymphatic collector, collecting lymph from most of the animal's body. More than ¾ of all lymph passes through it. To fill the thoracic lymphatic duct of goats, an intra-addular injection was used through the popliteal lymph node. At the level of the first rib, the thoracic lymphatic duct in this goat flows into the external jugular vein with one sleeve (mono trunk type) and several sleeves (deltoid type). The morphological composition of the central lymph in goats has been studied.
Keywords: Thoracic duct, topography, surgery, lymph, cannula, jugular vein, cell.